2019
DOI: 10.1111/apm.13008
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of tick‐borne transmitted tularemia on Southern Zealand, Denmark

Abstract: Francisella tularensis is a zoonotic bacterium which causes the infection tularemia. It colonizes invertebrates and vertebrates, counting wildlife animals and rodents. Humans can become infected through several pathways including contaminated food, water, and handling animals and due to bites from vectors. Ticks are known to cause tularemia in humans, though their role as a disease transferring vector is not well understood. We describe two case reports of tularemia transferred by ticks on Southern Zealand, De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…Table 6 summarizes data from tularemia case series with a predominance of the UG or GL forms. Many other sporadic UG or GL tularemia cases have been reported in several countries but with similar findings than those reported in case series ( Pérez-Castrillón et al, 2001 ; Jackson et al, 2012 ; Sobolewska-Pilarczyk et al, 2014 ; Boone et al, 2015 ; Formińska et al, 2015 ; Calin et al, 2017 ; Pekova et al, 2017 ; Whitten et al, 2017 ; Haulrig et al, 2020 ; Kubiliute et al, 2021 ). The UG and GL forms are predominant worldwide, except in some countries such as Turkey (see below).…”
Section: Tularemia Treatment In Humanssupporting
confidence: 81%
“…Table 6 summarizes data from tularemia case series with a predominance of the UG or GL forms. Many other sporadic UG or GL tularemia cases have been reported in several countries but with similar findings than those reported in case series ( Pérez-Castrillón et al, 2001 ; Jackson et al, 2012 ; Sobolewska-Pilarczyk et al, 2014 ; Boone et al, 2015 ; Formińska et al, 2015 ; Calin et al, 2017 ; Pekova et al, 2017 ; Whitten et al, 2017 ; Haulrig et al, 2020 ; Kubiliute et al, 2021 ). The UG and GL forms are predominant worldwide, except in some countries such as Turkey (see below).…”
Section: Tularemia Treatment In Humanssupporting
confidence: 81%
“…Due to environmental and climatic changes the geographical distribution of vector-borne infections is changing and incidences increasing [ 6 ]. F. tularensis has been detected in increasingly new settings and in a wide range of wild species [ [1] , [2] , [3] ] and more cases have recently been reported from Sweden and a few cases from Denmark [ 1 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroquinolones, tetracyclines and aminoglycoside are all effective therapy for F. tularensis with cure rates varying between 60–100 % [ 11 ], because of the toxicity of aminoglycosides and the need for intravenous administration, tetracyclines and fluoroquinolones are first-line drugs for treatment of mild to moderate tularemia and should be given for 14–21 days depending on clinical status [ 4 , 12 ]. Some studies have reported tetracyclines to have higher rates of relapse compared to fluoroquinolones [ 7 , 11 ]. Our patients both reported marked improvement of symptoms following antimicrobial treatment and no relapse or subsequent complications were seen, but they also reported to be suffering from fatigue, myalgia or shortness of breath the following 2–3 months.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the less virulent F. tularensis subsp. holarctica in European ticks has been described (19)(20)(21), but transmission of tularemia via ticks is relatively uncommon (53,75,76). Laboratory confirmation of tularemia consists of detecting the bacteria in a biological sample and/or detecting a specific antibody response.…”
Section: Tularemiamentioning
confidence: 99%